2013
DOI: 10.1371/journal.pone.0062050
|View full text |Cite
|
Sign up to set email alerts
|

Tribological and Antioxidation Synergistic Effect Study of Sulfonate-Modified Nano Calcium Carbonate

Abstract: A middle base number sulphonate-modified nano calcium carbonate (SMC) with an average size of 35 nm was synthesized, and its tribological and antioxidation synergistic behaviors with ashless antioxidant N-phenyl-α-naphthylamine (T531) in hydrogenated oil (5Cst) were evaluated. The results demonstrate that adding this synethesized additive even at a low amount (<2.0 wt.%) can evidently improve its load-carrying capacity by 1.5 times and enhance its antiwear performance; in addition, the friction-reducing effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Synergistic behavior of sulfonated calcium carbonate and an ashless antioxidant (N-phenyl-αnaphthylamine (T531)) in hydrogenated oil was investigated and the results suggested that anti-wear and antioxidant effect were synergistically improved in the system [40]. Figure 16.…”
Section: Antioxidants/additives Synergism and Antagonismmentioning
confidence: 99%
“…Synergistic behavior of sulfonated calcium carbonate and an ashless antioxidant (N-phenyl-αnaphthylamine (T531)) in hydrogenated oil was investigated and the results suggested that anti-wear and antioxidant effect were synergistically improved in the system [40]. Figure 16.…”
Section: Antioxidants/additives Synergism and Antagonismmentioning
confidence: 99%
“…The Zn2p peaks at 1022.2 and 1021.9 eV shows ZnS compound in the tribofilm . The peak Ca2p for 1 and 5% ZDDP+base oil corresponded to CaPO bonds, and the peak at 347.3 eV for 3% ZDDP+base oil shows the existence of calcium carbonate (CaCO 3 ) in the tribofilm …”
Section: Resultsmentioning
confidence: 98%
“…Reduction of the engine oil viscosity with increasing silica values from 2 g/L to 3 g/L (from 177.56 to 173.68 cSt, respectively) could be attributed to the deposition of the massive bulks and the reduction of their concentration in the engine oil. For calcite, it seemed that relatively large calcite particles (d<40 µm) were deposited in the engine oil [40], and they did not increase the concentration; thus, no significant effect on the oil viscosity was observed. Souza et al [41] found that with increasing the viscosity of engine, oil wear was enhanced.…”
Section: Resultsmentioning
confidence: 98%